PENGARUH PERSEPSI KUALITAS JASA DAN EMOSI KONSUMSI PADA EVALUASI KEPUASAN KESELURUHAN - , Fachri Eka Saputra, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study empirically examined the role of consumption emotions in the overall satisfaction model. Specifically, this study seeks to investigate the structural relationship between perceived service performance, consumption emotion and overall satisfaction. In the structural model, the effect of perceived service performance on overall satisfaction is mediated by the consumers emotional experience (positive and negative consumption emotions) as the evaluation of experienced service experience. Respondents are consumers fast food restaurants in the city of Yogyakarta. In this study researchers used three fast food restaurants as a sample object, which is McDonaldâs, Pizza-hut, and Hoka-hoka bento. The model in this study were tested by using two-step approach to structural equating modeling. The result show that the dimension of reliability, assurance, and physical evidence of the most important role in shaping perceptions of overall service performance in the fast food service industry. Positive and negative emotions partially mediate relationship between perceived service performance and overall satisfaction, which means the influence of perceived service performance on satisfaction will be stronger when consumers experience positive emotional experience result from the evaluation of the service they feel, while the opposite effect from perceived service performance on customer satisfaction will be reduced when consumers experience negative emotions associated with the experience of service they experience.